Family functioning internet addiction among students of a public school in North Lima - Adriano Rengifo, Cristian (2019)
Objetive: To determine the relationship between family functioning and Internet addiction adolescent studentsfrom a public school in northern Lima. Methods: non-experimental and cross-sectional design was usedcorrelational. An intentional non-probability sampling, including students of both sexes aged between 12 and20 years were also used. Results: 44% of adolescents have a family operation midrange and only 21.7% havean extreme performance. Also 86% of participants evidenced a normal Internet use, 13% are at risk of addictionand only about 1% are addictive Internet use. Furthermore, there was no significant relationship between thevariables of study (Chi = 4.079; p>.395), except for family cohesion (r = -.223, p<0.01). Conclusions: The familyfunctioning was not significantly related to Internet addiction. However, it was found that a negative relationshipwith family cohesion; that is the greater family cohesion, the lower the risk of internet addiction.